The source, quantity, and spatial distribution of interfacial water during glide-snow avalanche release: experimental evidence from field monitoring - Fees, Amelie; Lombardo, Michael; van Herwijnen, Alec; Lehmann Grunder, Peter Ulrich; id_orcid:0 000-0001-6315-7441; Schweizer, Jürg; id_orcid:0 000-0001-5076-2968 (Copernicus, 2025)
Glide-snow avalanches release at the soil-snow interface due to a loss friction which is suspected to be linked to interfacial water. Presently, the formation and distribution of the interfacial water are not well understood and glide-snow avalanches are considered unpredictable. We investigated the source, quantity, and spatial distribution of interfacial water before and during avalanche release through spatio-temporal field monitoring. The measurement setup consists of a sensor grid covering a slope with frequent glide-snow avalanche activity. The 24 grid sensors measured the soil temperature and liquid water content (LWC) throughout seasons 2021/22 to 2023/24. Snow and interfacial temperature and LWC were monitored locally with a vertical sensor profile ranging from the soil into the snow. Seven glide-snow avalanches released over the sensor grid and their investigation showed the following: (i) interfacial water originated from geothermal heat, rain, and meltwater percolation; (ii) the quantity of snow LWC was lower for glide-snow avalanches that released in early winter than in spring; (iii) soil temperatures in the release area were higher than in the remaining slope if interfacial water originated from geothermal heat; (iv) if interfacial water originated from rain and/or melt, we observed (locally) higher soil LWC in the release area; and (v) for the majority of observed avalanches the spatial variability in soil LWC across the slope reached a local minimum at the time of avalanche release. In the future, with continued monitoring, the spatio-temporal investigation of the soil LWC and temperature will help to quantify the drivers of glide-snow avalanche release at the slope scale. This will contribute to improved glide-snow avalanche forecasting and mitigation. ISSN:1994-0416 ISSN:1994-0424